SISTEM EKSTRAKSI KANDUNGAN URL, TITTLE, META TAG, HYPERLINK PADA HALAMAN WEB - Mahdiyah, Evfi (SEMIRATA 2015, 2015)
Web Extraction aims to obtain relevant keywords and gather important information from web content to be stored into database. The purpose of this study was to design and create a system that can extract the content URL, Tittle, Meta tags and hyperlinks on the element tag of a HTML document (web page). This system is a web-based application that utilizes techniques Regular Expression. Extraction results will be collected and organized in a database. The method used in this study includes four phases of activity, namely: data collection phase, phase analysis in the form of system design, system development and testing phase of this sistem. This system can collect information about the URL, Tittle, Meta Tag of web content to be stored into the database. Sistem expected to be used as collectors of important information from various types of web pages that spread across the Internet. Keywords : web extraction, HTML, URL, tittle, meta tags, hyperlinks